Treatment with iron increases weight gain and psychomotor development. - Aukett, M A (1986)
Previous work at this hospital and elsewhere has shown that anaemia in toddlers is common and is associated with psychomotor delay. It seemed unclear, however, whether this association was cause and effect or merely due to the same underprivileged environment. A double blind randomised intervention study was, therefore, performed. After an initial assessment 97 children with anaemia (haemoglobin 8-11 g/dl) aged 17-19 months received either iron and vitamin C or vitamin C only (control group) for two months and were then reassessed. The children who received the iron had an increased rate of weight gain and more of them achieved the expected rate of development. While iron deficiency anaemia is unlikely to be the only factor in the slower development of children living in underprivileged circumstances, it can at least be easily identified and treated. Routine child health surveillance in such areas should include a haemoglobin determination.